1976
DOI: 10.1007/bf01385944
|View full text |Cite
|
Sign up to set email alerts
|

Electrophilic substitution in phenanthroline coordinated to transition metal ions. Rates of nitration of some rhodium(III) and cobalt(III) complexes

Abstract: 67 SummaryThe rates of nitration in sulphuric acid of 1,10-phenanthroline coordinated to rhodium(Ill) and cobalt(Ill) in a number of complexes have been measured and found to be much greater in these complexes than in free phenanthroline under the same conditions. Relative rates are generally higher in those complexes which bear the smaller overall positive charges, but these charges may be modified by protonation of the other ligands in the complexes.Contrary to earlier reports, some other electrophilic subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1977
1977
1982
1982

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Jones et a/(7) however reported, that on coordination to cobalt(Ill), the rate of bromination of aniline (in [Co(en)2(aniline)x]n+ : n = 2, X = CI-; n = 3, X = OH2) decreases by a factor of 10 ~°. Recently Gillard, Houghton and Tucker (8) observed that 1,10-phenanthroline, coordinated to rhodium(Ill) and cobalt(Ill), undergoes nitration at a much faster rate than does free phenanthroline under comparable conditions. This paper reports the results of the study of the kinetics of iodination of salicylate in the bis-(ethylenediamine)-(salicylato)cobalt(lll) complex.…”
Section: Introductionmentioning
confidence: 99%
“…Jones et a/(7) however reported, that on coordination to cobalt(Ill), the rate of bromination of aniline (in [Co(en)2(aniline)x]n+ : n = 2, X = CI-; n = 3, X = OH2) decreases by a factor of 10 ~°. Recently Gillard, Houghton and Tucker (8) observed that 1,10-phenanthroline, coordinated to rhodium(Ill) and cobalt(Ill), undergoes nitration at a much faster rate than does free phenanthroline under comparable conditions. This paper reports the results of the study of the kinetics of iodination of salicylate in the bis-(ethylenediamine)-(salicylato)cobalt(lll) complex.…”
Section: Introductionmentioning
confidence: 99%